Analisis Kebutuhan E-Modul Pada Mata Pelajaran Fikih Kelas X Di MA Darul Ulum Palangka Raya - Afrianto, Afrianto; Wirayudha, Ramadhan (Edification Journal : Pendidikan Agama Islam, 2024)
This research aims to (1) identify the difficulties students face in the Islamic jurisprudence (fikih) subject; (2) present the teaching materials used in fikih learning; (3) assess the effectiveness of the teaching materials used by teachers in helping students understand the subject; (4) identify the topics that students find challenging in the fikih subject; (5) describe the needs analysis for the development of an e-module teaching material in the fikih subject at a secondary Islamic school (MA). In this study, the researcher applied the research and development (R&D) method using the 3D research method (define, design, develop), with a focus on the define stage. To collect information and data, the researcher used an online questionnaire distributed to tenth-grade students at MA Darul Ulum Palangka Raya. The analysis technique employed was qualitative descriptive analysis. Based on the survey responses, the researcher concluded that (1) the majority of students do not find the fikih subject difficult; (2) the teaching materials used in fikih include textbooks and worksheets (LKS); (3) the teaching materials used by fikih teachers have assisted students in understanding the material; (4) out of the nine fikih topics in the tenth-grade curriculum, two topics, namely the burial of the deceased (pemulasaran jenazah) and purification (taharah), are considered challenging by students; (5) 71.9% of students are interested in using an e-module for fikih learning.